Perspectives of Football Fans Towards Interaction Pattern And Conflict Management in Shin Tae-Yong's Leadership of The Indonesians National Football Team - Ariadi, Nana; Razak, Abdur (POLITEKNIK LP3I, 2024)
This research analyses the perspectives of football fans toward interaction pattern and conflict management in Shin Tae-Yong's leadership of the Indonesian National Football Team (Timnas). During his career journey, there are some dynamics of interaction and conflicts which occur between Shin Tae-Yong and the players, the staff and the federation. This research aims to describe the perspectives of football fans toward the interaction pattern and conflict management of Shin Tae-Yong as the head coach of Timnas. The research method which used is descriptive qualitative. The qualitative data gained through the questionnaire which spreaded to 150 football fans of the homeland at the age 20-45 years old and the deep interview to the 10 of 150 respondents who have filled in the questionnaire. The data analysis technique uses Miles and Hubberman method in order to interpret the qualitative data. The results of this research show Shin Tae-Yong has formal interaction pattern by prioritizing the discipline and upholding his authority as the head coach to the players, staff and federation. On the conflict management, Shin Tae-Yong uses 4 of 5 styles of management conflict toward the players, staff and federation.